COMPARISON OF EQUAL VALUE IN THE APPLICATION OF LEARNING EXAMPLES AND NON-EXAMPLES IN GRADE SEVEN - Nafisah K Zackiyah; Syaifudin; Luvi Antari (Jurnal Math-UMB.EDU, 2024)
One of the topics in mathematics is valued comparisons involving two or more variables, this material is often used in everyday life even so there are still many students who do not understand this material so that action is taken. This research is a class action research that implements the examples non examples learning outcomes of students on comparable value material. This research was conducted in II cycles, the initial cycle did not reach the research completeness criteria, namely 75% only reached a percentage of completenesss of 57,14% and in the second cycle there was an increase in the percentage of completeness reaching 78,56%. So in conclusion, the application of class action research with examples non examples learning model can improve the learning outcomes of students in class VII MTs Thawalib Sriwijaya Palembang. Keywords: learning outcomes, classroom action research, value comparison, examples non  examples